ANALISIS PEMELIHARAAN PREVENTIF AC PACKAGE PADA GERBONG KERETA PENUMPANG K1 DI DEPO 2 GERBONG KERETA BANDUNG - Gilang Muharam Pratama Putra; Andri Irawan (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2020)
This study aims to analyze the maintenance of AC Package preventive on the K1 passenger train car at Depo 2 of Bandung Rail Car. This research is a qualitative descriptive, using snowball sampling technique. Data collection techniques in this study were interviews, observation, and documentation. In this study using a validity test that is a triangulation of sources, triangulation of techniques and triangulation of time. The results showed that in maintaining the economic life of the AC Package is still not good and still found damage to the AC Package. In the supply of technicians, equipment and supplies are still not available as specified. There are still 44 technicians needed and the equipment is still in poor condition. in this case, the AC Package preventive maintenance activities on K1 passenger train cars still have a lot to be repaired at Depo 2 Bandung